Mott-Schottky Analysis of Laboratory Prepared Ag2S-AgI Membrane Electrode - Rajbhandari, A.; Manandhar, K.; Pradhananga, R. R. (Journal of Nepal Chemical Society, 2013)
Mott-Schottky analysis has been carried out to study the semiconducting behavior of Ag2S-AgI material, which is used as membrane material in iodide ion sensors. Polycrystalline Ag2S-AgI materials with mixing ratios 1:1wasprepared by co-precipitation method and Mott-Schottky analysis was carried out. The impedance was recorded using a Solartron 1280 Schlumberger frequency response analyzer at 5 KHz and 10 mV perturbing signal. A straight line with a positive slope is observed between + 0.2 V to -0.2 V (SSE) indicating n-type semiconductor behavior of polycrystalline Ag2S-AgI membrane. The donor concentration ND was calculated from the slope using dielectric constant of Ag2S-AgI. The values obtained are ~ 6 orders of magnitude lower than in metals. This is an important implication for the charge and potential distribution at the semiconductor/electrolyte interface. The Mott Schottky analysis hasshown that the present materials are n-type semiconductors with donor defect concentration of 7.4x1017/cm3. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8113 Journal of Nepal Chemical Society Vol. 28, 2011 Page: 89-93 Uploaded Date: May 24, 2013